Mastering Unity 2017 Game Development with C# - Second Edition - Thorn, Alan; Thorn, Alan (Packt Publishing, 2017)
Master realistic animations and graphics, particle systems, game AI and physics, sprites and VR development with Unity 2017About This BookCreate professional grade games with realistic animation and graphics, particle systems and game physics with Unity 2017Unleash the power of C# scripting to create intelligent game AI and professional grade game workflows.Create immersive VR games using the latest Unity 2017 VR SDK. Who This Book Is ForIf you are a Unity developer who now wants to develop and deploy interesting games by leveraging the new features of Unity 2017, then this is the book for you. Basic knowledge of C# programming is assumed.What You Will LearnExplore hands-on tasks and real-world scenarios to make a Unity horror adventure gameCreate enemy characters that act intelligently and make reasoned decisionsUse data files to save and restore game data in a way that is platform-agnosticGet started with VR developmentUse navigation meshes, occlusion culling, and Profiler toolsWork confidently with GameObjects, rotations, and transformationsUnderstand specific gameplay features such as AI enemies, inventory systems, and level designIn DetailDo you want to make the leap from being an everyday Unity developer to being a pro game developer? Then look no further! This book is your one-stop solution to creating mesmerizing games with lifelike features and amazing gameplay.This book focuses in some detail on a practical project with Unity, building a first-person game with many features. You'll delve into the architecture of a Unity game, creating expansive worlds, interesting render effects, and other features to make your games special. You will create individual game components, use efficient animation techniques, and implement collision and physics effectively. Specifically, we'll explore optimal techniques for importing game assets, such as meshes and textures; tips and tricks for effective level design; how to animate and script NPCs; how to configure and deploy to mobile devices; how to prepare for VR development; how to work with version control; and more.By the end of this book, you'll have developed sufficient competency in Unity development to produce fun games with confidence.Style and approachThis book takes an easy-to-follow, step-by-step tutorial approach. You will create an advanced level Unity game with an emphasis on leveraging advanced Unity 2017 features while developing the game in its entirety.